Building Primary-School Children's Resilience through a Web-Based Interactive Learning Environment: Quasi-Experimental Pre-Post Study - Nicolaidou, Iolie; Stavrou, Evi; Leonidou, Georgia (My University, 2021)
Resilience is a person's mental ability to deal with challenging situations adaptively and is a crucial stress management skill. Psychological resilience and finding ways to cope in crises is a highly relevant topic considering the COVID-19 pandemic, which enforced quarantine, social distancing measures, and school closures worldwide. Parents and children are currently living with increased stress due to COVID-19. We need to respond with immediate ways to strengthen children's resilience. Internet-based cognitive behavioral therapy interventions for children's stress management overcome accessibility issues such as the inability to visit mental health experts owing to COVID-19 movement restrictions. An interactive learning environment was created, based on the preventive program "Friends," to overcome accessibility issues associated with delivering cognitive behavioral therapy-based interventions in formal and informal education settings.
Keywords: COVID-19; interactive learning environment; Internet-based cognitive behavioral therapy; Parents; Prevention intervention; Primary school children; Psychological resilience; Teachers